Analisis Berita Acara Pemeriksaan dalam Penanganan Tindak Pidana Pencurian dengan Pemberatan di Kabupaten Lembata - Samara, Finsensius; Teme, Gracya Olivia; Botoor, Antonia Sisilia Bona; Utama, Putu Ade Bhaga; Ladoangin, Krispinus Junior Putra; Baon, Matheus Todo; Luna, Mario Paul Antonio (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
This study analyzes the criminal act of aggravated theft that occurred in Lembata Regency, Nubatukan District, Lewoleba Selatan Village, with a focus on the role of the Official Investigation Report (police investigation report) as the main instrument in the evidentiary process. As an official document that records the statements of victims, witnesses, and the perpetrator, the BAP serves as an essential basis for investigators, prosecutors, and judges in assessing the fulfillment of the elements of the offense. Based on an examination of the incident chronology, the methods of forced entry into the victim’s house, and the perpetrator’s control over the victim’s belongings, this study shows that the elements of Article 362 of the Indonesian Criminal Code (KUHP) are fulfilled, including the aggravating circumstances under Article 363 paragraph (1) points 3 and 5 of the KUHP, namely that the act was committed at night and involved breaking in.The research method employed is a literature study, examining criminal law literature, the KUHP, the KUHAP, expert legal doctrines, police investigation regulations, court decisions, and scholarly articles related to aggravated theft and the quality of BAP. The analysis is conducted qualitatively through normative interpretation of regulations and legal theories, particularly the theory of offense elements, the theory of criminal liability, and the theory of offense qualification. The findings confirm that the quality of the BAP greatly influences the success of the evidentiary process and the effectiveness of law enforcement. Therefore, the professionalism of investigators, accuracy in drafting the BAP, and synergy between authorities and the community are crucial factors in preventing and addressing aggravated theft in Lembata Regency.